Design of space with body interaction - ÖZBEK, DERYA ADIGÜZEL (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2018)
Humans as beings with body touch, connect with and interact with the world through their bodies. Relationship between humans and the world is defined via their body and the bodies are shaped in accordance with this relationship. Dynamic and interactive relationship between space and body has a vital role in design. Space should be designed for the user who experience instead of the standard production for static body. This study addresses the Space-Body Interaction course constructed in this understanding and the process of body-interactive space design developed within that course and its outcome products. The Space-Body Interaction course is provided as an undergraduate, shared elective course of Faculty of Architecture by Istanbul Kultur University (IKU), Department of Interior Architecture and Environmental Design. The course was planned in the same conceptual background and structure in the fall and spring terms of the academic year of 2016-2017. There are two objectives of the course: The first one is to inform students of the experience-based approaches of the space-body relationship. The second is to ensure transformation and internalization of the knowledge into a design product through a project process. To that end, the thinking systems that handle the space-body relationship which presents the conceptual background of both this study and this course in an experience-focused manner was put forth primarily. Next, process and outputs of the body-interactive space design, key concepts and perspectives of body-space interaction were addressed. The results of the study achieved within the context of course objectives were discussed in terms of body-space relationship, course objectives, student attainments and educational approaches.
Keywords: Body; Space; Space-Body Interaction; Experience; Interior Architecture Education